A structural analysis method for the management of urban transportation infrastructure and its urban surroundings. Issue 1 (1st January 2017) - Chatziioannou, Ioannis; Alvarez-Icaza, Luis
Abstract: Urban Transportation Infrastructure (UTI) is a key asset for any city as it affects economic growth and urban functioning; UTI is more valuable than ever due to the urbanization process that concentrates many people to the urban centers, generating a major mobility demand and car usage. Hence, an approach to UTI management is required, which would provide a greater significance to sustainable mobility. This paper's objective is to structure in hierarchical manner UTI and urban surroundings indicators related to sustainable mobility in order to create a decision-making instrument related to UTI management in the form of a weighted index and to evaluate public policies-strategies associated to these indicators. This was accomplished through the structural analysis-MICMAC method; the results showed which indicators are the most important and the necessity to prioritize them in order certain public policies to be more effective conforming to their impact on the weighted index.